M-lump waves and their interactions with multi-soliton solutions for the (3+1)-dimensional Jimbo-Miwa equation - Ismael, Hajar Farhan; El-Ganaini, Shoukry; Bulut, Hasan (Walter de Gruyter Gmbh, 2023)
In this work, the dynamical behaviors of the Jimbo-Miwa equation that describes certain interesting (3 + 1)-dimensional waves in physics but does not pass any of the conventional integrability tests are studied. One-, two-, and three-M-lump waves are constructed successfully. Interactions between one-M-lump and one-soliton wave, between one-M-lump and two-soliton wave as well as between two-M-lump and one-soliton solution are reported. Also, complex multi-soliton, solutions are offered. The simplified Hirota's method and a long-wave method are used to construct these types of solutions. The velocity of a one-M-lump wave is studied. Straight Lines of travel for M-lump waves are also reported. To our knowledge, all gained solutions in this research paper are novel and not reported beforehand. Moreover, the gained solutions are presented graphically in three dimensions to better understand the physical phenomena of the suggested equation.
Keywords: complex multi-soliton solutions; interaction phenomena; Jimbo-Miwa equation; long-wave method; M-lump waves